Liquefaction susceptibility and deformation characteristics of saturated coral sandy soils subjected to cyclic loadings – a critical review - Chen, Guoxing; Qin, You; Ma, Weijia; Liang, Ke; Wu, Qi; Juang, C. Hsein (Earthquake Engineering and Engineering Vibration, 2024)
Coral sandy soils widely exist in coral island reefs and seashores in tropical and subtropical regions. Due to the unique marine depositional environment of coral sandy soils, the engineering characteristics and responses of these soils subjected to monotonic and cyclic loadings have been a subject of intense interest among the geotechnical and earthquake engineering communities. This paper critically reviews the progress of experimental investigations on the undrained behavior of coral sandy soils under monotonic and cyclic loadings over the last three decades. The focus of coverage includes the contractive-dilative behavior, the pattern of excess pore-water pressure (EPWP) generation and the liquefaction mechanism and liquefaction resistance, the small-strain shear modulus and strain-dependent shear modulus and damping, the cyclic softening feature, and the anisotropic characteristics of undrained responses of saturated coral sandy soils. In particular, the advances made in the past decades are reviewed from the following aspects: (1) the characterization of factors that impact the mechanism and patterns of EPWP build-up; (2) the identification of liquefaction triggering in terms of the apparent viscosity and the average flow coefficient; (3) the establishment of the invariable form of strain-based, stress-based, or energy-based EPWP ratio formulas and the unique relationship between the new proxy of liquefaction resistance and the number of cycles required to reach liquefaction; (4) the establishment of the invariable form of the predictive formulas of small strain modulus and strain-dependent shear modulus; and (5) the investigation on the effects of stress-induced anisotropy on liquefaction susceptibility and dynamic deformation characteristics. Insights gained through the critical review of these advances in the past decades offer a perspective for future research to further resolve the fundamental issues concerning the liquefaction mechanism and responses of coral sandy sites subjected to cyclic loadings associated with seismic events in marine environments.